Identification of Fusarium spp. causing dry rot of seed potato tubers in northern, Thailand - Falert, S.; Akarapisan, A. (International Journal of Agricultural Technology, 2019)
Fusarium dry rot (FDR) is an important potato disease causing post-harvest tuber rot and seed piece decay worldwide. The causative agent of potato dry rot was identified in northern Thailand, based on the characterization and pathogenicity of the isolated pathogen. Infected potato tuber samples from different areas in northern Thailand showed potato dry rot symptom. Fusarium species were identified, based on morphology and the internal transcribed spacer (ITS) region of the nuclear ribosomal DNA (rDNA) and pathogenicity. The effect of wounding on infection by Fusarium species in potato tubers was studied, four injury levels were evaluated to determine the influence of wound severity on infection by each Fusarium species. F. graminearum and F. solani were isolated from diseased potato tubers in Chiang Mai and Tak Province in Thailand, respectively. F. graminearum was the most aggressive and exhibited typical external dry rot lesions expressed as brown to black flecks on the tuber surface. This is the first report to evaluate the importance of F. graminearum as potato pathogen in Thailand.